Identidade de gênero e sexualidade : uma análise das revistas Nova e Playboy - Montezelo, Giovana Gabriela (2013)
Sexuality is a topic that is becoming increasingly important for the construction of gender identity of individuals. The effort of this work is to identify how the media, especially Nova and Playboy magazines, transmits content about sexuality for men and women; the work analyzes some of the materials, dossiers and interviews in magazines present selected. The idea of \" new\" is part of several magazines in circulation in the Brazilian market. However, this idea of \" new\" offers a false sense of freedom when it is just the continuation of the placement of stereotypes . The theory developed around gender category contributes to the understanding of the construction of identities and also the extent to which femininity and masculinity has been aired by several speeches. Butler (2012), is the most important author because she shows that there is a matrix of intelligibility in which the genders are constructed. This matrix relates the coherence and continuity among sex / gender / desire / sexual practices; the dominant matrix in society is that of compulsory heterosexuality. The media provide role models that are consistent with this dominant matrix. Therefore it is necessary to understand how the media influences the construction of identities and dissemination of social representations about the stereotyped behaviors that would be feminine and masculine. The analysis of the magazines demonstrates that the \"new\" has to do with new ways to present content and not with a change in relationships and identities. Thus, the importance of the work lies in identifying what the media convey, or continue airing, whether they contribute or not to the questioning of the dominant heterosexual matrix, it offers new possibilities for relationships and new lifestyles .